(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the integration of collaborative learning strategies with creative teaching methods in English language classrooms. It highlights how groupbased activities, peer-to-peer interactions, and project-based tasks can enhance learners’ engagement, motivation, and linguistic competence. The study emphasizes the role of creativity in fostering deeper understanding, improving communication skills, and encouraging critical thinking. Practical examples and case studies are presented to demonstrate how collaborative and creative approaches can transform traditional ESL teaching into a dynamic and student-centered experience. The findings suggest that combining collaboration and creativity not only improves language acquisition but also nurtures learners’ confidence and social skills.